Identification of Student Misconceptions Using Four Tier Diagnostic Instruments On Straight Motion Materials - Erlangga, Sony Yunior; Winingsih, Puji Hariati; Saputro , Handoyo (COMPTON: Jurnal Ilmiah Pendidikan Fisika, 2021)
This study aims to identify the quantity of students who misconceptions on the material of Straight Motion. The research subjects were 30 students of class X MIA 1 of Yogyakarta SahabatQu High School with purposive sampling technique. This type of research is a quantitative descriptive study with data collection techniques carried out by triangulation namely documentation of test results, interviews and questionnaires. The research instrument used was a three-tier test. the results of the most frequent misconception sequences were found in vertical motion (26%), speed and speed (18%), GLB (17%), distance and displacement (16%), and GLBB (15%). Based on the results of the interview showed the same thing.